Association between Toxoplasma gondii Infection in Brain and a History of Depression in Suicide Decedents: A Cross-Sectional Study - Cosme Alvarado-Esquivel; Laura Alejandra Mendoza-Larios; Fernando García-Dolores; Luis Francisco Sánchez-Anguiano; Elizabeth Irasema Antuna-Salcido; Jesús Hernández-Tinoco; Adriana Rocha-Salais; Marcela Araceli Segoviano-Mendoza; Antonio Sifuentes-Álvarez (Pathogens, 2021)
We assessed the association between Toxoplasma gondii (T. gondii) infection of the central nervous system and suicide correlates in suicide decedents. Eighty-seven decedents who died by suicide received in a forensic setting for medico-legal autopsies in Mexico City were studied. Two samples of brain (amygdala and prefrontal cortex) from each decedent were examined for detection of T. gondii using immunohistochemistry. Correlates of suicide including a history of previous suicide attempts, co-morbid mental disorder, consumption of alcohol or tobacco, irritability and aggression, economic problems, presence of drugs or alcohol in blood and suicide method were obtained and analyzed for their association with T. gondii infection. T. gondii immunohistochemistry was positive in prefrontal cortex sections in 6 decedents and in an amygdala section in one decedent. Thus, the prevalence of T. gondii infection in brain in suicide victims was 8.0% (7/87). Bivariate and logistic regression analysis of suicide correlates showed that only a history of depression was associated with T. gondii infection of the brain in suicide victims (OR: 12.00; 95% CI: 2.26–63.46; p = 0.003). Our results provide evidence that T. gondii infection in brain is associated with a history of depression in suicide decedents.